Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $p$ be prime number ($p\gt2$) and $a,b\in\mathbb Z$ ,$a+b\neq0$ ,$\gcd(a,b)=1$ how to prove that $$\gcd\left(a+b,\frac{a^p+b^p}{a+b}\right)=1~~\text{or}~~ p$$

Thanks in advance .

share|cite|improve this question
See also…, and other questions linked there. – Martin Sleziak Mar 22 '14 at 7:04
up vote 7 down vote accepted

$\rm\displaystyle \left(a\!-\!b,\frac{a^p\!-b^p}{a-b}\right) = (a\!-\!b,\,a^{p-1}\!+\cdots+b^{p-1}) = (a\!-\!b,\color{#C00}{pb^{p-1}}) = (a\!-\!b,p)\:$ by $\rm\:a\equiv b\ \ (mod\ a\!-\!b)\:$ and $\rm\:(a,b) = 1\:\Rightarrow\: (a\!-\!b,b) = (a,b)=1\ \cdots\:\Rightarrow\:(a\!-\!b,b^n) = 1\ $ by Euclid's Lemma.

Remark $\ $ It's a special case $\rm\ f(x) = x^p,\,\ x = a\ \ (so\ \ \color{#0A0}{f'(b)} = \color{#C00}{pb^{p-1}})\:$ of

Theorem $\rm\displaystyle\quad \frac{f(x)-f(b)}{x-b} \: \equiv\ \color{#0A0}{f\:'(b)}\ \ \ (mod\ \:x\!-\!b)\quad$ for $\rm\ f(x)\in \mathbb Z[x]$

Proof $\ $ By Taylor, $\rm\,\ f(x)\ =\ f(b) +\: f\:'(b)\ (x\!-\!b) \,+\, (x\!-\!b)^2\: g(x)\ \ $ for some $\rm\ g(x) \in \mathbb Z[x]$

share|cite|improve this answer
Note: this is meant as a (big) hint, along with some conceptual background for further motivation. If you have any trouble filling in the details then please feel welcome to ask questions in comments, and I will gladly elaborate. – Math Gems Mar 25 '13 at 20:05
See also this answer. – Bill Dubuque Apr 22 '15 at 15:26

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.